The Role of Institutes of Consecrated Life in the Service of Peace - Ujhazi, Lorand (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2025)
The Catholic Church played an invaluable role in promoting peace during the 20th century. However, it is important to note that the Catholic Church is a hierarchical community and a mystical body, comprising members who engage in the work of peace in diverse ways. This paper will focus on the role of institutes of consecrated life. This study will examine the relationship between these institutions and the promotion of peace in the context of the various legally binding documents. In addition to an examination of legal and theological principles, the study also considers the practical realities and identifies areas where legal provisions are insufficient. It then makes suggestions for improvements. The hypothesis is that the institutions of consecrated life form an integral part of the constitutional order of the Church. Consequently, they promote the Church’s common objectives, enriching them with specific, even meta-juridical aspects and capacities due to their legal status and charism. However, their position within the Church also represents the limit of their activities.